Pengembangan Video Game Edukasi Interaktif Dalam Meningkatkan Pengetahuan Tentang Kesehatan Jantung - Rayhan Elfandika Ramadhani; Rahadian Kurniawan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Heart disease is one of the leading causes of death worldwide. Various factors can influence heart health, such as an unhealthy lifestyle. The importance of heart health lies in the fact that the heart plays a vital role as the primary pump in the body's circulatory system. Education and awareness about heart health are crucial. Effective educational programs can help improve public knowledge about the risk factors, signs, and symptoms of heart disease. This research aims to develop an interactive educational video game that can enhance public knowledge about heart health. The video game is designed considering effective educational and interactive aspects to provide an engaging learning experience. The development method used is Rapid Application Development (RAD), which includes requirements planning, user interaction, system development, as well as evaluation and testing. During its development, accurate and reliable information about heart health is conveyed through narration, appealing visual displays, quizzes that encourage players to understand essential concepts, and feedback that provides information and motivation. This research is expected to contribute to enhancing public understanding of heart health through an innovative and enjoyable approach